Pembentukan Kelompok Pendukung Asi (Kp-Asi) Tingkatkan Cakupan Asi Dan Mpasi - Rohmayanti Rohmayanti; Margono Margono; Herma Fanani Agusta; Wina Amelia Rinjani; Nikita Cahyani; Titi Wijayanti; Yunia Luthfi Rana (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2020)
The purpose of community service (PPMT) is to form a breastfeeding support group (KP-ASI) consisting of health cadres and supported by the head of village and midwives of health center so as to improve the coverage of exclusive and a food making skills for escort or MP-ASI, in addition to this activity, aims to hone the skills of students in the Community service program. Implementation method with participatory community empowerment through Apraissal Participatory Rural model is approach in the process of empowerment and improvement of community participation, activities conducted in the form of socialization of activities on all elements of the village related, the establishment of the structure of KP-ASI, lactation management training, assistance cadres practice management skills of lactation in Posyandu, training of MP-ASI skills, guidance of cadres in Posyandu practice of MP-ASI skills, evaluation or monitoring of activities through the lactation management competition and MP-ASI between cadres as a form of evaluation. The results of this activity in the form of the structure of KP-ASI organization with SK from the village head, there is an increase in the knowledge and skills of cadres in the management of lactation and MP-ASI. The test result of pre posttest in the test with value P = 0.00 (< 0.05) indicates that the knowledge of participants significantly increased. The results of the competition between cadres in the presentation of MP-ASI show the result that cadres can properly prepare MP-ASI. Data from village Midwives stated that there was an increase in BREAST feeding and MP-ASI in Sidoagung village.